Ultrasound Guided Nerve Blocks for Anterior Cutaneous Nerve Entrapment Syndrome an Overlooked Cause of Chronic Abdominal Pain: A Case Series - Rayamajhi, Anuj Jung; Hamal, Pawan Kumar; Bhattarai, Prajjwal Raj; Paudel, Subash Chandra; Paudel, Prashanta; Dhungel, Bidur; Yadav, Rupesh Kumar; Pokhrel, Nabin; Timilsina, Sarika (Journal of Nepal Health Research Council, 2022)
Entrapment abdominal neuropathy is not a common diagnosis in our context. Chronic Abdominal wall pain is often mistaken for gastritis, gynecological issue, thoracic spinal radiculopathy, rectus sheath hematoma, abdominal muscle injury or psychiatric disorder. Anterior cutaneous nerve entrapment syndrome is one of the frequent causes of abdominal wall pain occurring due to trapped thoracic intercostal nerves between abdominal muscles. History and bedside Carnett’s sign can elicit the diagnosis. Injection of the local anesthetics with steroids in the junction between the rectus sheath and abdominal muscle under ultrasound guidance can provide sustained pain relief. We should consider Anterior cutaneous nerve entrapment syndrome as a differential diagnosis while evaluating the abdominal wall pain.Keywords: ACENE; carnett’s test; chronic abdominal pain; entrapment neuropathy; hydrodissection.